2015
DOI: 10.1590/0074-02760150051
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara canis and the allergic process

Abstract: The protective effect of infectious agents against allergic reactions has been thoroughly investigated. Current studies have demonstrated the ability of some helminths to modulate the immune response of infected hosts. The objective of the present study was to investigate the relationship between Toxocara canis infection and the development of an allergic response in mice immunised with ovalbumin (OVA). We determined the total and differential blood and bronchoalveolar lavage fluid cells using BALB/c mice as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Not surprisingly the mobilization of repair mechanisms is host-parasite specific [39], and several distinct pathways of tissue repair have been described. Yet, there is a paucity of studies of assessing tissue recovery in response to acute toxocariasis [5,6,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly the mobilization of repair mechanisms is host-parasite specific [39], and several distinct pathways of tissue repair have been described. Yet, there is a paucity of studies of assessing tissue recovery in response to acute toxocariasis [5,6,40].…”
Section: Discussionmentioning
confidence: 99%
“…Once in the small intestine of intermediate hosts (it can be paratenic hosts, such as humans or mice), larvae penetrate the gut wall and migrate to many organs, including the lung, liver, muscles, and central nervous system, resulting in significant pathology. Infection in the lung with T. canis L2 larvae can cause an asthma-type condition in children [3,4]; airway hyperresponsiveness, pulmonary inflammation, and increased levels of IgE can persist for months in mice experimentally-infected with T. canis [5,6]. Thus, assessing the inflammatory response, including defining roles for cells such as classically activated macrophages (M1) in the pathology following infection with T. canis is critical to a better understanding of the disease and the development of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of allergic manifestations in patients with toxocariasis is controversial among Brazilian researchers. Zaia et al 53 observed acute allergic inflammation of the airways of mice infected by T. canis. Silva et al 54 reported a patient with Loeffler syndrome who had been infected by T. canis.…”
Section: Frequency and Characteristics Of Human Infections Due To Toxocaramentioning
confidence: 99%